These Girls want to sell you a Raffle ticket (Cimarron Legend, 1992)
Clipping reads : These girls want to sell you a raffle ticket. (b tof) Victoria Fernandez, Ashely Sanchez, and Katrina Fernandez are running for the esteemed title of Bazaar Queen, on the occasion of the Immaculate Conception Parish's annual bazaar. The crowning will occur at the church's community center at 9:00 Saturday night. The winner will be determined by who ha raised the most money for the church. (By the way, have you bought your raffle tickets yet?)
Newspaper clipping and Photograph of Victoria Fernandez, Ashely Sanchez, and Katrina Fernandez
Mater List Item # 13
File location is in the New Mexico File Cabinets
Keywords: Fernandez, Victoria; Sanchez, Ashely; Fernandez, Katrina; Immaculate Conception Parish; Annual Bazaars; Church Community Functions; Raffle Tickets; Church Fund Raisers; Bazaar Queens; Cimarron, New Mexico